Slant spacelike ruled surfaces and their Bertrand offsets - Almoneef, Areej A.; Abdel-Baky, Rashad A. (Frontiers in Physics, 2024)
In this work, we investigate the synthesis problem of slant spacelike ruled surfaces and associated Bertrand offsets (BO) in E13 (Minkowsk 3-space). We provide the parametric equation for a non-developable spacelike ruled surface (SLRS) by using the Blaschke frame (BF). This results in the amplitude to control a family of curvature functions defining the domestic form of this SLRS. Therefore, we found the appropriate SLRS criteria to be slant SLRS. Thus, several new Bertrand offsets (BO) for slant SLRS are investigated and constructed.